Circadian rhythms in the renin-angiotensin system and adrenal steroids may contribute to the inverse blood pressure rhythm in hypertensive TGR(mREN-2)27 rATS - Lemmer, Björn; Witte, Klaus; Schänzer, Anne; Findeisen, Anke (Chronobiology international, 2000)
The transgenic TGR(mREN-2)27 rat is not only characterized by fulminant hypertension, but also by a disturbance in circadian blood pressure regulation, resulting in inverse circadian blood pressure profiles. The reasons for these alterations are not very well understood at present. We therefore investigated the circadian rhythms in several hormones participating in blood pressure regulation. From TGR and Sprague-Dawley (SPRD) control rats synchronized to 12h light and 12h dark (LD 12:12) blood was collected at different circadian times (07, 11, 15, 19, 23, 03, and 07 again, 5 rats per strain and time). The activities of plasma renin and converting enzyme, as well as plasma concentrations of corticosterone and aldosterone, were determined by radioimmunoassay (RIA). SPRD rats showed significant circadian rhythms in all variables except plasma renin activity, with maxima occurring during the day. TGR rats showed significant circadian rhythmicity in plasma renin activity and corticosterone and daily variation in aldosterone; angiotensin-converting enzyme (ACE) activity did not reach statistical significance. In TGR rats, 24h means in plasma renin activity and aldosterone were approximately sevenfold and fourfold higher, respectively, than in SPRD rats. Peak concentrations in corticosterone around 15h were more than two times higher in TGR rats than in SPRD rats, whereas no differences were observed during the night. It is concluded that, in TGR rats, the overall increase in plasma renin activity and aldosterone may contribute to the elevated blood pressure. The comparatively high levels in corticosterone and plasma renin activity during daytime may be involved in the inverse circadian blood pressure profiles in the transgenic animals. (Chronobiology International, 17(5), 645-658, 2000)
Published online: 07 Jul 2009
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 14.04.2022